Fundamental analysis of self-healing phenomena in asphalt mixtures - Leworthy, Samuel C. (2022)
When asphalt becomes cracked it will slowly begin a self-healing process, during which, the crack is either partially or fully repaired over a period of time. Upon reaching a certain temperature the bitumen in the asphalt becomes a Newtonian fluid and the rate of this self-healing is greatly increased. This research discusses ways to model this process using flow within a porous medium and using the results produced to compare current popular methods of triggering self-healing in asphalt.